PROSPECTIVE STUDY OF CLINICAL OUTCOME OF FRACTURE SHAFT FEMUR IN CHILDREN TREATED WITH TITANIUM ELASTIC NAILING: OUR RESULTS - SHELENDRA, SAIYAM; KISHOR, UIKEY; SHAILENDRA, CHOUHAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Introduction: Femur fracture in children between 5 and 15 years is a common injury with a variety of operative and non-operative management options. There remains debate as to the optimal treatment for a given patient and fracture. Our aim was to assess functional outcome of a large number of patients after their femur fractures with a titanium elastic nailing (TEN). Methods: This was a prospective randomized study comprised 50 patients with displaced diaphyseal femur fractures treated with TEN. Two nails were used in fracture. The patients were followed up at 2nd week, 1 month, 3 months, and 6 month after surgery. Results were evaluated by flynn’s scoring criteria at each follow-up visit. Results: At the end of 6 months, out of 50 patients, excellent result was achieved in 45 patients (90%) and good in five patients (10%). No poor outcome seen. Intramedullary fixation by Tens is an effective treatment of fracture of femur in properly selected patients of the 5–15 years age group. Conclusion: The treatment with femoral shaft fracture in children between the age group of 5–15 years by titanium elastic nail is ideal as it hastens fracture union, reduce rate of mal union, shortening, and allow early rehabilitation.